Optimized prediction of cognition based on brain morphometry across the adult life span - Tsapanou, A. (Neurobiol Aging, 2020)
We set out to map the combined and unique contributions of five different biomarkers for two cognitive outcomes in cognitively healthy adults. While probing the association of biomarkers with cognition in the full experimental sample is essential, we focused on how well any such associations would persist in held-out data. 335 cognitively normal participants, age 20-80 years older, with a mean of 16 years of education were included in the study. Z-scores were computed for fluid reasoning and vocabulary. The following imaging data were included: brain volume-thickness, fractional anisotropy, deep grey matter volume, and white matter hyperintensity. Volume accounted for most of the variance in both cognitive domains. In out-of-sample data, fluid reasoning was best predicted by volumes, but vocabulary by the combination of all modalities. While the predictive utility improves overall for older participants, the information gleaned relative to null-models becomes less for older participants. An optimized set of brain biomarkers can predict cognition in out-of-sample data, to various degrees for both fluid and crystallized intelligence.